Improvement of motility after culture of testicular spermatozoa: the effects of incubation timing and temperature - Hosseini, Akram; Khalili, Mohammad Ali (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Background: Sperm motility is the reliable parameter that roles in success of intracytoplasmic sperm injection (ICSI), especially in azoospermia. Selection of appropriate culture duration, temperature and media for enhancing the sperm motility is an important issue in assisted reproduction program. The aim was to evaluate the sperm motion characteristics after culturing of testicular sperm extraction (TESE) samples at different temperatures and time intervals. Methods: In this prospective study, 27 TESE samples were collected from young azoospermic patients. The samples were cultured in Ham’s F10+20% HAS, at different temperatures (incubation at 37 vs. 25 ℃) and sperm total motility was assessed at different time intervals of 0, 24, 48 and 72 h post testicular biopsy. Results: In vitro culture at 25 ℃ changed sperm motility from 13% immediately after biopsy to 76% at 24 h, 43% at 48 h and 15% at 72 h. At 37 ℃, the sperm motion feature was changed to 67% at 24 h, 38.40% at 48 h and 12.03% at 72 h. Sperm motility change at 24 h was incremental in both conditions of culturing, but significant at 25 ℃ (P≤0.05). Conclusions: The ideal in vitro culture for testicular spermatozoa was at 25 ℃ after 1 day of culture, which optimized the sperm motility in azoospermic TESE samples.